Revealing the structural heterogeneity of metallic glass: Mechanical spectroscopy and nanoindentation experiments. (1st July 2021) - Tao, K.; Qiao, J.C.; He, Q.F.; Song, K.K.; Yang, Y.
Abstract : The correlations of the structural heterogeneity, internal friction and STZs of MG were established. Based on the cooperative shear model and statistical analysis, the scale variation of the STZs was revealed. The spatial structural heterogeneity can be enhanced by severe plastic deformation. Abstract: Microstructural heterogeneity is an important issue in understanding the mechanical and physical properties of metallic glasses (MGs). Theoretically, physical aging below the glass transition temperature relax the MGs systems to a lower potential energy state on the potential landscape (PEL) while the cold rolling rejuvenates MGs to a higher potential energy state. In the current work, we systemically turned the structural heterogeneity through dynamic mechanical relaxation and rejuvenation. Correlations among the structural heterogeneity, internal friction, and shear transformation zones (STZs) of the model alloy was connected. Based on the cooperative shear model and statistical analysis, the scale variation of the STZs was revealed. This study demonstrated that the spatial structural heterogeneity can be enhanced by severe plastic deformation which can reduce the energy barrier for STZs activation. And we proposed the barriers decrease and more nucleation sites of STZs from physical aging to rejuvenation, which may be potential mechanism for improving the plasticity in MGs. Graphical abstract: Image, graphical abstract